The Effects of Age, Burn, and Physiotherapy Services on the Developmental Status of Children With Burn Injuries - Neda Orakifar; Razieh Mofateh; Maryam Kiani Haft Lang; Noshin Kashisaz; Amal Saki Malehi (University of Social Welfare and Rehabilitation Sciences, 2024)
Objective Children, especially at the age of <4 years, are one of the high-risk groups facing burn injuries. In addition, childhood is an important time for children's growth and development because during this period, children acquire many skills in different areas of motor, cognitive, and social performance. Accordingly, this study investigates the effects of age, burn, and the amount of physiotherapy services on the developmental status of children under 5 years of age with burn injuries using the ages and stages questionnaire. Materials & Methods In this cross-sectional study, conducted using a descriptive-analytical method, information was extracted on 93 children under 5 years of age with second and third-degree burn injuries who were admitted to Ahvaz Accident and Burn Hospital, in Ahvaz City, Iran. The electronic link of the ages and stages questionnaire, which is one of the most common and widely used tools for measuring children's developmental status, appropriate to the child's age group was sent to one of the parents. They were asked about the number of physiotherapy sessions after discharge by phone. Results The area of fine movements showed the highest frequency of developmental delay (8.25%). The results of the Mann-Whitney analysis showed that the mean age of children with fine movement disorders (area 3) was higher (P=0.016) and more time had passed since their burns (P=0.019) compared to healthy people. No statistically significant difference was observed between the number of sessions receiving physiotherapy services during hospitalization (P=0.74) and discharge (P=0.69) between these two groups. Conclusion Burns is one of the influential factors in the delay of children's developmental status, which involves motor development (fine and gross movements) and problem-solving. Movement disorder is more common in old age. Also, as more time passes since the burn, the delay of fine movements is more visible.